2008
DOI: 10.1158/1541-7786.mcr-07-0191
|View full text |Cite
|
Sign up to set email alerts
|

Geldanamycin-Induced Down-Regulation of ErbB2 from the Plasma Membrane Is Clathrin Dependent but Proteasomal Activity Independent

Abstract: ErbB2, a member of the epidermal growth factor receptor family, is overexpressed in a number of human cancers. In contrast to the epidermal growth factor receptor, ErbB2 is normally endocytosis resistant. However, ErbB2 can be down-regulated by inhibitors of heat shock protein 90, such as geldanamycin. We now show that geldanamycin induces endocytosis and lysosomal degradation of full-length ErbB2. We further report that

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
70
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(76 citation statements)
references
References 49 publications
4
70
1
1
Order By: Relevance
“…S4). This is consistent with the notion that full-length ErbB2 was endocytosed (36,37). ErbB2 was eventually degraded on incubation of the cells with geldanamycin as shown by Western blots using antibody to an intracellular epitope (Fig.…”
Section: Erbb2 Is Endocytosed On Incubation With Geldanamycin In Cellsupporting
confidence: 90%
See 2 more Smart Citations
“…S4). This is consistent with the notion that full-length ErbB2 was endocytosed (36,37). ErbB2 was eventually degraded on incubation of the cells with geldanamycin as shown by Western blots using antibody to an intracellular epitope (Fig.…”
Section: Erbb2 Is Endocytosed On Incubation With Geldanamycin In Cellsupporting
confidence: 90%
“…1B). Previous studies have shown that incubation with geldanamycin induces clathrin-dependent endocytosis of ErbB2 (37) and that ErbB2 in cells incubated with geldanamycin localizes to early as well as to late endosomes (36,37). Geldanamycin-induced endocytosis of ErbB2 was confirmed by immunoelectron microscopy experiments.…”
Section: Erbb2 Is Endocytosed On Incubation With Geldanamycin In Cellmentioning
confidence: 59%
See 1 more Smart Citation
“…It is however controversial how this takes place. Some studies have suggested that Hsp90 inhibitors enhance the clathrin-dependent or clathrin-independent endocytosis of ErbB2 (54,55). Other studies suggest that ErbB2 is constitutively internalized, and that HSP90 inhibitors do not influence this rate but instead promote sorting of ErbB2 away from the recycling pathway and into lysosomes (46,51).…”
mentioning
confidence: 99%
“…Because it relies on Hsp90 for stable expression, exposure of ErbB2/HER2-expressing cells to an Hsp90 inhibitor such as geldanamycin leads to rapid internalization, ubiquitination, and degradation of the protein (Mimnaugh et al 1996;Lerdrup et al 2006). Pedersen et al (2008) have argued that ubiquitination of ErbB2/HER2 following inhibition of Hsp90 is essential for presentation of the internalized protein to the lysosomes for degradation. Concurrent treatment of ErbB2/HER2-expressing cells with geldanamycin and lactacystin, a well known proteasomal inhibitor, rescues ErbB2/HER2 from degradation and results in the accumulation of internalized, ubiquitinated protein (Lerdrup et al 2006).…”
Section: Discussionmentioning
confidence: 99%